(untitled) (Orfeu, 2020)
Analytical studies (formal or unpretentious) taken as a motto for a conversation between composers, seeking to amplify a poetics of contagion. From Deleuze and Guattari’s (1997) and Ferraz’s (2007) readings, the concept gives an image to think the small dialogues that permeate the creation process, focusing on the conversation between composers, which can occur verbally, but mainly through its works, when musical analysis is commonly used. In the composition of two pieces, the author used analytical studies to establish such conversations and dialogues. In Inquietações, the contagion occurred through the technical and musical strategies, in dialogues mainly with two Berio’s Sequenzas. In Tons de amarelo patético, the composition occurred in parallel with the analysis of Lima’s Antiphonas; this analysis allowed to observe the contagion as a modus operandi of the piece. One can think in a poetics of contagion, which spreads epidemically through analysis and conversations.